Estimación del riesgo sistemático de las acciones del ipecu y aplicación de modelos de heteroscedasticidad condicional autorregresiva - Hidalgo Andrade, Juan Eduardo (2009)
The objective of this paper is estímate both the asset’s sistematic risk from IPECU and the relation between self returns and market returns measured by the parameter form the classical CAPM model. The origina lestimations was regressed by Ordinary Least Squares giving good outcomes about the significance. Afterwards in order to describe effectively the economic behavior of financial market, we use th Box-Jenkins and Engle’s methodology well kown as Autorregresive Conditional Heteroskedasticity Model, which consists in leaving the homoskedasticity assumption and explain the series’s disturbances based on its lagged and after introduce the estimated disturnaces’s volatitily in the expression that explainthe stock’s returns. In analysis regression we find that companies’s returns could be modelated using an ARCH process being the Cervezería Nacional the company which shows the best results in the risk estimation and the description of the behavior of its returns.The objective of this paper is estímate both the asset’s sistematic risk from IPECU and the relation between self returns and market returns measured by the parameter form the classical CAPM model. The origina lestimations was regressed by Ordinary Least Squares giving good outcomes about the significance. Afterwards in order to describe effectively the economic behavior of financial market, we use th Box-Jenkins and Engle’s methodology well kown as Autorregresive Conditional Heteroskedasticity Model, which consists in leaving the homoskedasticity assumption and explain the series’s disturbances based on its lagged and after introduce the estimated disturnaces’s volatitily in the expression that explainthe stock’s returns. In analysis regression we find that companies’s returns could be modelated using an ARCH process being the Cervezería Nacional the company which shows the best results in the risk estimation and the description of the behavior of its returns.